Early Neurotoxic Effects of Inorganic Arsenic Modulate Cortical GSH Levels Associated With the Activation of the Nrf2 and NFκB Pathways, Expression of Amino Acid Transporters and NMDA Receptors and the Production of Hydrogen Sulfide - Silva-Adaya, Daniela; Ramos-Chávez, Lucio Antonio; Petrosyan, Pavel; González-Alfonso, Wendy Leslie; Pérez-Acosta, Alegna; Gonsebatt, Maria E. (Frontiers in Cellular Neuroscience, 2020)
Exposure to toxic metals and metalloids is an important cause of preventable diseases worldwide. Inorganic arsenic (iAs) affects several organs and tissues, causing neurobehavioral alterations in the central nervous system (CNS) that might lead to neurodegeneration. In this work, we wanted to explore the time and dose-related changes on GSH levels in several regions of the CNS such as the cortex, striatum, hippocampus, and cerebellum, to identify the initial cellular changes associated to GSH depletion due to iAs exposure. Mice received a single intraperitoneal injection containing 5 or 14 mg/kg sodium arsenite. Animals were sacrificed at 2, 6, and 24 h. Significant depletion of GSH levels was observed in the cortex at 2 and 6 h while on the striatum, hippocampus or cerebellum regions no significant changes were observed. GSH depletion in the cortex was associated with the activation of the Nrf2 and NFκB pathways, which led to the upregulation of xCT, EAAC1, GLAST and GLT-1, and the activation of the transsulfuration pathways which led to the overproduction of H2S in the cortex and increased levels of GSH in the cortex and cerebellum at 24 h. In the cortex, the NMDA receptor subunits NR2A and NR2B were also altered at 24 h. These early effects were not homogeneous among different brain regions and indicate early neurotoxic alterations in the cortex and cerebellum.